Proyecto para retomar en su totalidad el servicio de practicaje de la autoridad portuaria de Guayaquil - Álava Gutiérrez, Humberto Rafael (2009)
This project aims to resume the pilotage service, which in principle was the responsibility of Port Authority of Guayaquil (PAG), which was responsible for its administration. Currently the pilotage service is charge of private companies, which provide for the Port Authority of Guayaquil who decided it was more efficient if the service was provided by these companies. Among them include: Ecuadorian PILOT, SERNAPRA, PACIFIC PILOT, CISENI. Our project is focused on known as the Port Authority of Guayaquil can resume pilotage service, and what would be the socio-economic impact that this project would be carried out. The pilotage service is being offered to all ships entering the Simon Bolivar Port of Guayaquil and other private terminals. This service is the main tool for people called “PRACTICAL”, which are solely responsible for the vessels to enter the various docks. The main role of PAG as a state is “to serve”, for this reason Port Authority of Guayaquil should return to this pilotage service, once the grant or when you consider that you can provide this service efficiently.